Islamic Education Construction in the Perspective of Falsification of Karl R. Popper - Abd. Rahim Razaq; Umiarso Umiarso (The Faculty of Tarbiyah and Teacher Training associated with PSPII, 2019)
Epistemology as a branch in philosophy has an important position in science including in Islamic education. This research critically examines the epistemological construction of Islamic education through a perspective of falsification which was coined by Karl R. Popper. This research used a qualitative approach to the type of literature study and analyzes data through a productive hermeneutical approach. The conclusion of this research shows that scientific epistemology needs to be designed to understand the theories, concepts, and propositions of the Islamic education system. Scientific epistemology contains the verificative-philosophical logic and intuition-revelation logic (Qur'an and al-Hadith. This epistemology has a rational-critical, empirical, intuitive, and prophetic (illahiyah) dimension and it is called Prophetic Criticism. The implication is that Islamic education will have an integrative view of the profane (physical) and transcendental (metaphysical) side. Islamic education is the logical-superlogical content of subjective-objective thinking, the world of theory-supratheory, and critical argumentation with a rational-intuitive foundation of self and outside self-views.